If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5k + 6g = 2k Reorder the terms: 6g + 0.5k = 2k Solving 6g + 0.5k = 2k Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-0.5k' to each side of the equation. 6g + 0.5k + -0.5k = 2k + -0.5k Combine like terms: 0.5k + -0.5k = 0.0 6g + 0.0 = 2k + -0.5k 6g = 2k + -0.5k Combine like terms: 2k + -0.5k = 1.5k 6g = 1.5k Divide each side by '6'. g = 0.25k Simplifying g = 0.25k
| z/5-4=1/5/6 | | 0.23= | | 17/13=x/10 | | -7(-3b+11)+9(-2-3b)-(-5b-8)=-37 | | x-36=44.9 | | x/4-5=7/8 | | 0.217/7 | | 5x+10(x+3)=15 | | 3/6z-6 | | 5x+4y^2= | | 41+2n=2+n | | x^2(x-2)+7x(2-x)-10(2-x)= | | -x(x-3)+x(-2x-8)= | | x^3+15x^2+6x+1=0 | | 9x3/2 | | 9(2+t)-7(t+1)= | | Y=28x-2xsquared | | 5h+6(2h+10)=10 | | 3x-2(5x-y)-(4y+x)= | | w^2(w-3)=350 | | 5x-22=26+x | | Y^2-2y= | | 3.4+z=-7 | | -6th-7=17 | | 1/3x-1/7=8 | | x^2+38x+361=36 | | 5xy-3y+10x-6= | | x-2(x+1)=5+9 | | 15/2x+4=-2 | | 12t=16 | | 2x^2+xy-y^2=2 | | (2c)(3c)=6c |